ANALISIS PENGARUH PENDAPATAN, KESESUAIAN HARGA, PEMAHAMAN AGAMA, DAN ETIKA KONSUMSI ISLAM TERHADAP KEPUTUSAN PENGGUNAAN HIJAB (Studi Kasus Mahasiswi Muslim Universitas Brawijaya Malang) - Yayanriani, Ica; Wiguna, Atu Bagus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Lifestyle requires people to follow every detail of the changes in this modern era. Fashion is a weapon in every appearance, whether fashion or hijab. The increasingly varied hijab fashion encourages Muslim teenagers to use the hijab which is a trend in today's era. Along with consumer desires that change into a lifestyle, the pattern of consumption will also change. The impression in the hijab that looks fashionable and attractive makes the hijab not only used as a cover for genitalia but as a style of dress that looks attractive and modern. Hijab is no longer a necessity but a desire to follow fashion trends. The results of the analysis show that income and price suitability do not have a positive influence on the decision to use the hijab. Where there are two variables that have a positive and significant influence on the decision to use hijab, namely the variable of religious understanding and Islamic consumption ethics, which means that someone who uses the hijab will pay attention to ethics in consumption and pay attention to religious understanding. The higher a person's religious understanding, the lower his decision-making in wearing the hijab, on the contrary, the lower the religious understanding, the higher the decision-making in wearing the hijab.